St. Nicholas church of Rudnevo in Tula district – a monument of Russian architecture of the fi rst half of the 18th century - Severtseva, Inga V. (Actual Problems of Theory and History of Art, 2025)
St. Nicholas church of the village Rudnevo in Tula district was until very recently unknown by scientifi c society. The church, which is now inaccessible, belongs to the group of centrally planned octoconch churches of Peter the Greats’ era, built in the county of the tsar’s closest allies. The date of construction of St. Nicholas church is unknown. All that we know is that its sanctification took place in 1755, as indicated by an inscription on its iconostasis. However, analyzing the forms and proportions of the architectural monument we can conclude that the construction work started earlier and was delayed.